The Role Of Kiyai In The Development Of Halal Tourism And Culinary In Islamic Boarding Schools - Wakit, Saipul (Jurnal Penelitian IPTEKS, 2024)
In its development, Islamic boarding schools experience transformation and evolution in accordance with the needs and developments of the times. Basically, Islamic boarding schools are a place for religious learning and a center for Islamic preaching. However, in its development, Islamic boarding schools continue to innovate and be creative in order to survive and serve the educational needs of the community. One innovation is that Islamic boarding schools are not only educational institutions but also provide tourist and culinary attractions. This certainly cannot be separated from the role of the kiyai in managing it. This view attracts researchers to reveal and study the role of kiyai in making this happen. In substance, this research focuses on analyzing the role of kiyai as managers, motivators, administrators and evaluators in tourism and culinary development. The research method uses a qualitative approach using data mining techniques through observation, documentation and interviews. The research results explain that kiyai have a strategic role in pioneering the development of Sharia-based natural tourism. The efforts made by the kiyai include training, workshops, comparative studies, increasing comfort and security, cultivating sharia tourism and halal culinary, cadre management, empowering students. In leadership, he carries out his role as a manager by planning, coordinating, implementing and evaluating work programs with his subordinates. The role of the kiyai evaluator is active in evaluating activities to determine the successes and obstacles of the planned program. The role of the kiyai as a motivator is very strategic because in Islamic boarding school culture the fatwa or instructions of the kiyai as motivation must be carried out. The role of the kiyai is as an administrator by being the pioneer of orderly administration. All forms of administration must be based on the direction, guidance and knowledge of the kiya